2020
DOI: 10.1177/2150135120918541
|View full text |Cite
|
Sign up to set email alerts
|

Improved Technique for Interventional Extracardiac Fontan

Abstract: We have previously reported a simple technique for preparatory staging and subsequent interventional completion of an extracardiac Fontan procedure that anatomically and hemodynamically closely mimics a standard extracardiac Fontan. We describe herein modifications that simplify the original procedural sequence and that may allow wider application. Percutaneous completion can be achieved even without a radiofrequency probe, using electrocautery. Fenestration is also easy to perform if there is a clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The creation of an extracardiac Fontan was reported in humans using a similar approach in 2017 and 2020. Reports in the literature involve, however, small numbers of patients with limited follow-up intervals ( 78 , 79 ).…”
Section: Percutaneous Fontan Completionmentioning
confidence: 99%
“…The creation of an extracardiac Fontan was reported in humans using a similar approach in 2017 and 2020. Reports in the literature involve, however, small numbers of patients with limited follow-up intervals ( 78 , 79 ).…”
Section: Percutaneous Fontan Completionmentioning
confidence: 99%
“…In the 50 years following the introduction of the procedure named after Francis Fontan (1), the indications as well as the surgical techniques have substantially evolved. The Fontan operation, which may be performed with various surgical techniques, is the final stage of surgical palliation for functionally univentricular hearts (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). A surgically created fenestration (or connection) between the Fontan circuit and the atrial cavity to reduce excessively elevated systemic venous pressures and to improve cardiac output by increasing the filling of the single ventricle may be beneficial in the immediate postoperative period (21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] In 2017 and 2022, Prabhu et al reported two cases using this technique where the surgical preconditioning was done in old children (5 and 11 years young). 15,16 We report here a very innovative approach for transcatheter extracardiac Fontan completion to allow preparation at an early age.…”
mentioning
confidence: 99%